Description of Metalimnobia (Metalimnobia) charlesi sp. n. from Europe (Diptera, Limoniidae) - Salmela, Jukka; Starý, Jaroslaw (Entomologica Fennica, 2008)
The cranefly species Metalimnobia (Metalimnobia) charlesi sp. n. is described from Europe, and a photograph of the wing and illustrations of the male terminalia are provided. This new species is closely related to M. (M) quadrimaculata (Linnaeus), but it can be distinguished by differences in some external and genital characters. The larva of the new species is most probably saproxylic, being associated with polyporous fungi on decaying deciduous trees. M. (M) charlesi sp. n. is known from Finland, Slovakia and Sweden.